Health economic evaluation of a medication safety intervention in elderly care: identifying causal effects in a multi-center quasi-experimental study design - Langenberger, Benedikt; Siegel, Martin; Busse, Reinhard; Vogt, Verena (BMC health services research, 2025)
The high prevalence of multimorbidity in the aging population necessitates complex medication regimens, increasing the risk of adverse drug events (ADEs) and hospital admissions. This paper evaluates an intervention aimed at improving medication safety for northeastern and western Germany under real-world conditions, thereby providing a pragmatic approach to the challenges of multi-center studies with staggered intervention starts and voluntary participation. The analysis utilizes iterative Propensity Score Matching (PSM) followed by a Difference-in-Differences (DiD) estimator to navigate the methodological complexities and assess the intervention’s effectiveness and cost-effectiveness. Results reveal a significant reduction in ADE-related hospital admissions by 27.5% and overall hospital admissions by 17.5%. We find that the intervention is cost-effective at an incremental cost-effectiveness ratio (ICER) of €15,169.66 per averted ADE and €4,180.61 per averted hospital admission. This study illustrates for evaluating complex health interventions in real-world settings and underscores the importance of balancing health outcomes improvements with economic considerations in aging populations.